2020
DOI: 10.1038/s41598-020-65691-w
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Glucose Deprivation on ATP and Proteoglycan Production of Intervertebral Disc Cells under Hypoxia

Abstract: As the most common cause of low back pain, the cascade of intervertebral disc (IVD) degeneration is initiated by the disappearance of notochordal cells and progressive loss of proteoglycan (PG). Limited nutrient supply in the avascular disc environment restricts the production of ATP which is an essential energy source for cell survival and function such as PG biosynthesis. The objective of this study was to examine ATP level and PG production of porcine IVD cells under prolonged exposure to hypoxia with physi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(33 citation statements)
references
References 86 publications
1
32
0
Order By: Relevance
“…In some studies, high oxygen has been observed to reduce the rate of glycolysis which is known as a positive Pasteur effect 20,94 . However, a number of other studies have shown a negative Pasteur or no effect for NP cells 8,14 . Despite IVD cells preferring a more prevalent glycolytic pathway for energy in its harsh microenvironmental conditions, the reasons for differences in observed phenomenon under varying nutrient concentrations remain unclear.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In some studies, high oxygen has been observed to reduce the rate of glycolysis which is known as a positive Pasteur effect 20,94 . However, a number of other studies have shown a negative Pasteur or no effect for NP cells 8,14 . Despite IVD cells preferring a more prevalent glycolytic pathway for energy in its harsh microenvironmental conditions, the reasons for differences in observed phenomenon under varying nutrient concentrations remain unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have reported oxygen consumption rates (OCR), 8–10,12 glucose consumption rates (GCR), and lactate production rates (LPR) for NP cells from animals and humans under varying nutrient conditions 8,10,13,14,17,34,35 . Tabulated rates from these studies can be found in Table S2–S4.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Some researchers have demonstrated the effect of glucose concentration on regulating the chondrogenic and osteogenic differentiation potential of CESCs to affect the differentiation of CESCs, which may represent a target for CE degeneration therapy ( Sun et al, 2019 ). Furthermore, to adapt to the changes in the microenvironment, IVD progenitors correspondingly change their metabolism by increasing matrix synthesis and anaerobic glycolysis in low glucose conditions (5 mM), which allows generating energy while producing less reactive oxygen species (ROS) and consuming less O 2 ( Yin et al, 2020 ).…”
Section: The Role Of Microenvironment In the Application Of Stem Cell...mentioning
confidence: 99%
“…No adverse events were found in clinical trials, and relief of pain was noted in the injection group compared to discectomy alone on a 2-years follow-up. Furthermore, patients who underwent discectomy and autologous disc chondrocyte transplantation were proved to have less adjacent segment disease than those who underwent discectomy alone (Yoshikawa et al, 2010). In another clinical trial, autologous MSCs were injected into the disc of 13 patients followed for 1 year as part of a pilot study.…”
Section: Clinical Applications and Future Perspectivesmentioning
confidence: 99%